Front Cover: A novel deep reinforcement learning enabled agent for pumped storage hydro‐wind‐solar systems voltage control. Issue 16 (7th December 2021) - Huang, Qin; Hu, Weihao; Zhang, Guozhou; Cao, Di; Liu, Zhou; Huang, Qi; Chen, Zhe
Abstract : The cover image is based on the Original Article A novel deep reinforcement learning enabled agent for pumped storage hydro‐wind‐solar systems voltage control by Weihao Hu et al., https://doi.org/10.1049/rpg2.12311 .